Використання електромобілів як таксі - Бодак, В. І.; Bodak, V. (ЦНТУ, 2023)
У статті розглянута методика зарядки електромобілів, що використовуються як таксі у Луцьку, та вирішення даної проблеми у інших містах. Основним фактором при виборі марки та моделі електромобіля для служби таксі є вартість транспортного засобу, рівень деградації тягової батареї та комфорт пасажирів. У країнах Західної Європи та Північної Америки популярністю користуються автомобілі виробника Tesla. В цих автомобілях використовуються тягові батареї ємністю від 70 кВт/год. Дані автомобілі є дорогими, тому у країнах з меншими рівнем достатку використовуються дешевші електромобілі з батареями меншої ємності. У Луцьку компанія «Преміум сервіс» експлуатує електромобілі марки Nissan Leaf з батареями 24 кВт/год. Зростання кількості електромобілів створило ряд проблем, оскільки, кількість станцій для заряджання у місті не зросла пропорційно кількості машин. Однієї нічної зарядки батареї електромобіля-таксі на підприємстві «Преміум сервіс» не вистачає для роботи протягом робочого дня. Тому у робочий час автомобілям доводиться дозаряджатись на міських електрозаправних станціях. In connection with the significant increase in the number of cars with internal combustion engines in Ukrainian cities, there is an increase in emissions of harmful gases, which significantly exceed permissible standards. The increase in the number of electric cars has been accelerated by the fact that when clearing an electric car, it is not necessary to pay value added tax and customs duty, but only excise duty for each kilowatt of battery capacity. The cost of one kilometer covered by an electric car is several times lower than a car with an internal combustion engine. In cities, taxi services are appearing that use only electric cars. The main factor when choosing the brand and model of an electric vehicle for taxi service is the cost of the vehicle, the level of degradation of the traction battery and the comfort of passengers. Tesla cars are popular in Western Europe and North America. These cars use traction batteries with a capacity of 70 kWh or more. These cars are expensive, so less affluent countries use cheaper electric cars with smaller batteries. In Lutsk, the "Premium Service" company operates Nissan Leaf electric vehicles with 24 kWh batteries. The increase in the number of electric cars has created a number of problems, since the number of charging stations in the city has not increased in proportion to the number of cars. One nightly charging of the battery of an electric taxi at the "Premium Service" enterprise is not enough to work during the working day. Therefore, during working hours, cars have to be recharged at city gas stations. The article discusses the method of charging electric cars used as taxis in Lutsk, and the solution to this problem in other cities.
Use of Electric Vehicles as Taxis
Keywords: електромобіль; зарядна станція; таксі; електродвигун; літій-іонна батарея; electric car; charging station; taxi; electric motor; lithium-ion battery